Multimodal Literacy: A Proposal for Didactic Exploration of Multimodal Text in Portuguese Language Classes (Revista de Estudos da Linguagem, 2024)
This article aims to analyze a multimodal text, the tweet, in the light of Visual Design Grammar (GDV) aiming to propose didactic-pedagogical suggestions from a critical (multi)literacies perspective. The corpus of analysis consists of the text “Ataque a tiros em escola do ES: Por que ataques em escolas têm se repetido no Brasil?”, published on Twitter by Jornal do Estado de São Paulo (Estadão) in November 2022. The procedures of analysis comprise: i) analyzing and describing, based on GDV, the representational, interactive and compositional meanings that make up the image resources of the text (Kress; van Leeuwen, 2020) and ii) presenting a proposal for didactic exploration to be developed in Portuguese language classes, based on Pedagogy of Multiliteracies (Kalantzis et al., 2020).